Peningkatan Kecerdasan Anak Usia Dini Melalui Pembelajaran Integratif Sains dan Al-Qur’an - Rohman, Baeti; Aziz, Jamil Abdul; Hikmah, Nurul; Alam, Mufassirul; Muhit, Abdul (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Improving Early Childhood Intelligence Through Integrative Learning of Science and the Qur'anThe Qur'an and science are a whole that cannot be separated. The Al-Quran supports humans to think logically regarding the existence of various things around them, especially regarding the creation of this universe. Likewise, science is created from human critical thinking about the objects around it. This integrative learning model needs to be introduced early on to children at the Early Childhood Education level. This research aims to see the impact of science and religion integrative learning for early childhood. This research is a qualitative-phenomemological research with the research object Raudhatul Athfal Bait Qurany Attafkir, Ciputat. This study found that, 1) the learning process is carried out in an integrative manner, such as conducting science experiments on students and then explaining the facts contained in the Al-Qur'an, 2) the concept of integration of science and the Qur'an in RA Bait Qur'any tends to systematic synthesis, namely instilling the concept indirectly to students that scientific objects are God's creation. The process of learning science is an effort to observe, classify, analyze and take lessons in order to build knowledge and lead to belief in the oneness of Allah and encouragement to be bound by Allah's rules. This research proves that science learning that integrates with the Qur'an can be taught from an early age. Science learning is friendly to children's growth and development because learning is not only built on the logic of thinking in the Qur'an but also based on developmental psychology and the level of thinking of early childhood. The integration of science and Al-Qur'an learning in RA Bait Qur'any is in thematic form with an experimental learning approach, logical thinking, and stimulates five children's intelligences, namely religious, moral, social, emotional and cognitive intelligence